1986
DOI: 10.2166/wst.1986.0083
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Treatment and Recycling of Oil Refinery Wastewater

Abstract: The objective of the present investigation was a high level of purification of the wastewater from an oil refinery achieved by using some improved methods yielding an effluent suitable for recycling into the process. All the investigations were carried out on a continuous laboratory pilot system consisting of the following units: dissolved air flotation (DAF), sedimentation, double-stage microbiological reactor, and adsorption columns filled with granular biologically activated carbon (GBAC). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It was found that over 50% of the COD and color could be successfully removed from this effluent (Jackson-Moss et al 1992). Miskovic et al (1986) carried out the treatment of oil refinery waste water using adsorption columns filled with granular biologically activated carbon. A high degree of COD reduction close to 100% (precisely, 99.9%), as well as removal of nitrogen compounds of 72% was achieved during a relatively short retention time within the range of 15-16.5 h. Suzuki et al (1996) applied biological activated carbon treatment to a type of wastewater collected from plating industries.…”
Section: Industrial Waste Watermentioning
confidence: 99%
“…It was found that over 50% of the COD and color could be successfully removed from this effluent (Jackson-Moss et al 1992). Miskovic et al (1986) carried out the treatment of oil refinery waste water using adsorption columns filled with granular biologically activated carbon. A high degree of COD reduction close to 100% (precisely, 99.9%), as well as removal of nitrogen compounds of 72% was achieved during a relatively short retention time within the range of 15-16.5 h. Suzuki et al (1996) applied biological activated carbon treatment to a type of wastewater collected from plating industries.…”
Section: Industrial Waste Watermentioning
confidence: 99%